RAB26 contributes to the progression of non-small cell lung cancer after being transcriptionally activated by SMAD3. Issue 4 (1st April 2022) - Ren, Haixia; Yang, Bo; Li, Mingjiang; Lu, Chunling; Li, Xiaoping
ABSTRACT: Non-small cell lung cancer (NSCLC) accounts for 85% of all cases of lung cancer, which constitutes the leading cause of cancer mortality. RAB26, a member of Rab GTPase superfamily, has been suggested to play a role in the tumorigenesis of NSCLC. The present work aimed to explore whether and how RAB26 contributed to the progression of NSCLC. NSCLC cell line A549 was transfection with short hairpin RNA (shRNA) or overexpression (Ov) vector to knockdown RAB26 or overexpress SMAD3, respectively. Then the malignant processes of A549 cells including proliferation, migration, invasion and apoptosis were evaluated by CCK-8, colony formation, wound-healing, transwell and TUNEL assays, respectively. Expression of proteins involved in these processes was measured by western blot. A549 xenograft mice model was established to confirm the effect of RAB26 silence on NSCLC progression in vivo. The relationship between RAB26 and SMAD3 was analyzed by bioinformatics and then verified by dual-luciferase reporter and chromatin immunoprecipitation (ChIP) assays. We found that silence of RAB26 inhibited the proliferation, migration and invasion but promoted apoptosis of A549 cells. In vivo studies revealed that the tumor growth of A549 xenograft was markedly suppressed upon RAB26 silence. Moreover, it was confirmed that SMAD3 bound to the promoter of RAB26 and enhance its expression. Finally, we observed that overexpression of SMAD3 significantly blocked the inhibitory effect of RAB26 silence on NSCLC progression. Collectively, RAB26 may contribute to the progression of NSCLC after being transcriptionally activated by SMAD3. Graphical Abstract: uf0001